2021
DOI: 10.1108/bij-07-2020-0389
|View full text |Cite
|
Sign up to set email alerts
|

Impact of overconfidence bias in stock trading approach: a study of high net worth individual (HNI) stock investors in India

Abstract: PurposeThe purpose of the study is to check whether Indian high net worth individual (HNI) investors are suffering from overconfidence bias in personal life and in-stock investment approach. The study is to benchmark an ideal behaviour that an investor should exhibit under the overconfidence bias.Design/methodology/approachBoth qualitative and quantitative methods were used to study the Indian HNI investors with overconfidence bias. As a first step, an exploratory study was conducted to identify the variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Experiments revealed that overconfidence acts as a mediator between representative heuristics and the investment decision; biases that were identified had a significant impact on investments made. Parhi et al (2021) researched the overconfidence bias and the impact of biases on the investments of high net-worth individuals (HNWIs). Their findings revealed that overconfidence bias had only a minor impact on investors' day-to-day lives as well as their decision-making processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Experiments revealed that overconfidence acts as a mediator between representative heuristics and the investment decision; biases that were identified had a significant impact on investments made. Parhi et al (2021) researched the overconfidence bias and the impact of biases on the investments of high net-worth individuals (HNWIs). Their findings revealed that overconfidence bias had only a minor impact on investors' day-to-day lives as well as their decision-making processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Investors were found to be accurate in their forecasts (Islam Khan et al, 2016;Du and Budescu, 2018). This accuracy rate and the belief system that they are better than others make the investors overconfident while trading in the stock market (Parhi and Pal, 2022). This behavioral bias in investors put a spin on rationality in investors making them influenced by these cognitive traits (Naveed and Taib, 2021).…”
Section: Overconfidence Biasmentioning
confidence: 99%
“…Further studies highlighted the importance of research into diverse investor biases and documented their impact on investor behaviors (Chong et al, 2021;Gong et al, 2021;Mittal, 2022) hence offering an unconventional approach to the financial markets (Pattnaik et al, 2022;Rahman and Gan, 2020). Present unbridled conditions in financial markets indicate that overconfidence bias (OB) appears to be one of the most influential bias among various investor biases (Jain et al, 2020;Parhi and Pal, 2022;Sachdeva et al, 2022) Retail investors exhibit uncertainty about their investment decisions in the financial market, thus underreacting to the information and eventually ending up making a mountain out of a hill (Chi and Li, 2019;Wang et al, 2004). In all other investor-related biases, OB contributed to the conundrum among investors in the Indian financial market (Mushinada and Veluri, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations